2013
DOI: 10.1038/nature12397
|View full text |Cite
|
Sign up to set email alerts
|

Changes in North Atlantic nitrogen fixation controlled by ocean circulation

Abstract: In the ocean, the chemical forms of nitrogen that are readily available for biological use (known collectively as 'fixed' nitrogen) fuel the global phytoplankton productivity that exports carbon to the deep ocean. Accordingly, variation in the oceanic fixed nitrogen reservoir has been proposed as a cause of glacial-interglacial changes in atmospheric carbon dioxide concentration. Marine nitrogen fixation, which produces most of the ocean's fixed nitrogen, is thought to be affected by multiple factors, includin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

10
84
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 86 publications
(94 citation statements)
references
References 39 publications
10
84
0
Order By: Relevance
“…These authors also reported a poor relationship between N 2 fixation and dust deposition from a global database (Luo et al, 2012), suggesting that iron is not the ultimate controlling factor of marine diazotrophy on a global basis (Luo et al, 2014). This implies that while empirical evidence suggests dust explains short-term diazotrophic responses, it cannot explain N 2 fixation rates on a basin-scale or over geological time-scales in the NA (Straub et al, 2013).…”
Section: Responses To Atmospheric Dust Inputsmentioning
confidence: 99%
“…These authors also reported a poor relationship between N 2 fixation and dust deposition from a global database (Luo et al, 2012), suggesting that iron is not the ultimate controlling factor of marine diazotrophy on a global basis (Luo et al, 2014). This implies that while empirical evidence suggests dust explains short-term diazotrophic responses, it cannot explain N 2 fixation rates on a basin-scale or over geological time-scales in the NA (Straub et al, 2013).…”
Section: Responses To Atmospheric Dust Inputsmentioning
confidence: 99%
“…Foraminifera-bound δ 15 N was measured at Princeton University following the protocol described in (23,32). In the intervals where foraminifera abundances were adequate, samples were measured in duplicate.…”
Section: Foraminifera-bound δ 15 N Analysismentioning
confidence: 99%
“…During nitrate uptake, phytoplankton preferentially consume N can be biased due to diagenetic alteration and contamination by foreign N input, with evidence for major artifacts from these processes in sediment records from both lowand high-latitude sites (11,12). The δ 15 N of organic matter bound within diatom and foraminifera microfossils avoids these issues and has been applied to reconstruct the nitrate consumption in the AZ and SAZ of the Southern Ocean, respectively (12,13).…”
mentioning
confidence: 99%